2010
DOI: 10.1109/tasl.2010.2051354
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Precedence Effect Modeling for Source Separation in Reverberant Environments

Abstract: Abstract-Reverberation continues to present a major problem for sound source separation algorithms. However, humans demonstrate a remarkable robustness to reverberation and many psychophysical and perceptual mechanisms are well documented. The precedence effect is one of these mechanisms; it aids our ability to localise sounds in reverberation. Despite this, relatively little work has been done on incorporating the precedence effect into automated source separation. Furthermore, no work has been carried out on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 14 publications
0
50
0
Order By: Relevance
“…We modified parameters g and α P of the precedence model to achieve an optimal performance on the target system (Polish ASR) during the preliminary tests. It was found that fixed values other than those suggested by Hummersone (Hummersone et al, 2010) can provide better results. In our optimisation both parameters were increased for the 16 kHz signals, gain factor by 6% to g = 0.825, and the time constant by 100% to α P = 12.5.…”
Section: Precedence Maskmentioning
confidence: 90%
See 2 more Smart Citations
“…We modified parameters g and α P of the precedence model to achieve an optimal performance on the target system (Polish ASR) during the preliminary tests. It was found that fixed values other than those suggested by Hummersone (Hummersone et al, 2010) can provide better results. In our optimisation both parameters were increased for the 16 kHz signals, gain factor by 6% to g = 0.825, and the time constant by 100% to α P = 12.5.…”
Section: Precedence Maskmentioning
confidence: 90%
“…It is based on the perceptual emphasis of the first wave front and has been implemented to both dereverberate and separate speech signals (Palomaki et al, 2004). We tested and implemented a precedence model developed by (Hummersone et al, 2010).…”
Section: Dereverberation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each source signal was a 27s speech signal made by concatenating utterances chosen from the TIMIT database [21] (one different speaker for each source). As mixing filters, we used binaural room impulse responses from [22] having RT 60 ≈ 0.68s. We generated two types of mixtures: Mix-DC where all sources are emitting continuously.…”
Section: Discussionmentioning
confidence: 99%
“…The precedence effect is also applied and modeled as a low pass filter with an inhibitory gain and time constant to mitigate the reverberant energy from the signal and to improve the separation performance in [17]. However, the model parameters are required to be estimated based on the room properties which are not always known as a priori.…”
Section: Relation To Prior Workmentioning
confidence: 99%